Clinical and laboratory differences and role of gene xpert in tuberculous pleural effusion - Shah, Manoj Kumar; Baral, Sushil; Bhattarai, Tulsi (Journal of Advances in Internal Medicine, 2021)
Background: The diagnosis of pleural effusion and its cause are essential for pleural fluid analysis. We have evaluated clinical and laboratory differences among the tubercular pleural effusion. Methods: The cross-sectional, observational hospital based study was conducted in Bir hospital, Nepal. All patients were evaluated by clinically and laboratory investigations. Patients enrolled for study have pleural effusion and pleural fluid analysis indicative of an exudative pleural effusion using lights criteria. The criteria of enrollment of the patients were pleural fluid for Adenosine deaminizes value more than 40 IU/L, positive for gene xpert test and pleural effusion of any cases with sputum positive pulmonary tuberculosis. Patients were divided into two groups lymphocytic and neutrophilic predominant pleural effusion. Results: Among 100 patients with diagnosis of exudative tubercular pleural effusion, the most common symptom was pleuritic chest pain in 85%, followed by fever in 84% and cough in 82%. Among the tubercular pleural effusion, 21% had neutrophils predominant and 79% had Lymphocytes predominant. The patients with neutrophil predominant Tubercular pleural effusion had higher fever rates (90.5vs.82.5%) than those with lymphocyte-predominant Tubercular pleural effusion. The mean value of Neutrophil predominant pleural fluid for lactate dehydrogenase (LDH) level was 1657.5 IU/L and protein was 5.3gm/dl and in lymphocyte predominant pleural fluid for LDH value was 610.2 IU/L and protein was 4.6 gm/dl; the difference was statistically significant with P value of <0.001. Only 15% of patients had sputum positive for Acid fast bacilli. Among the sputum positive patients, 47% had positive for pleural fluid for gene xpert test with all patients had rifampicin sensitive. The sensitivity of pleural fluid for gene xpert test was 46.6%, and specificity was 90%. Conclusion: In pleural effusion, the positivity of gene xpert for pleural fluid was higher among the sputum positive patients. The prevalence of Neutrophil-predominant pleural effusion was common in tubercular pleural effusion.